Assessment of color tea by innovative method - Petrusha, Oksana; Usatyuk, Nadia (My University, 2016)
The work is devoted to determining the color of tea computer colorimetry on a complex metric yellowness index.
Keywords: кафедра експертизи харчових продуктів; забарвлення; чай; якість; tea; color; quality